Two new species of Apteroscelio Kieffer (Hymenoptera: Scelionidae) from India - Kamalanathan, Veenakumari; Talamas, Elijah J.; Keloth, Rajmohana; Mohanraj, Prashanth (Zootaxa, 2017)
Two new species of Apteroscelio Kieffer, a previously monotypic genus, are here described, illustrated and keyed. Affinities between Apteroscelio and other scelionine genera are discussed. The male of this genus is imaged and described for the first time.